Peralihan Status Sertipikat Hak Pakai Barang Milik Daerah Menjadi Hak Guna Bangunan Dalam Pembangunan Mega Mall Kota Bengkulu - Annisa Nur Indar Parawangsa; Chintia Riduan Putri; Evan Nurrahman; Anisah Julianty W; Hanifah Laras Prahesti (GLOBAL SCIENTS PUBLISHER, 2026)
The conversion of land rights from Right of Use (Hak Pakai) attached to Regional Government Property (Barang Milik Daerah/BMD) into Building Use Rights (Hak Guna Bangunan/HGB) represents a juridical issue in the Indonesian agrarian legal system. The development of Mega Mall in Bengkulu City illustrates problems in the management and utilization of regional land assets that may create legal uncertainty and potentially cause regional financial losses if not conducted in accordance with the law. This study aims to analyze the legal mechanism for converting BMD Right of Use into Building Use Rights, identify the legal problems that arise, and formulate its juridical implications. This research employs statutory and conceptual approaches. The results show that such conversion must follow the mechanisms regulated in the Basic Agrarian Law, Government Regulation Number 40 of 1996, Government Regulation Number 28 of 2020, and the Minister of Home Affairs Regulation Number 19 of 2016. Any deviation from these mechanisms may lead to legal uncertainty, land disputes, and legal liability for authorized officials.